Politics of Economy: The Case of China's Involvement in Africa - Masud, Matiul Hoque; Ahmmed, Helal Uddin; Mostafa, Muhammad Ridwan; Choudhury, Anwar Hossain (Mediterranean Journal of Social Sciences, 2013)
China's economy based engagement with Africa has some political dimensions. China's political intention is to fill up the powervacuum in Africa, raising a new great game with Western and European powers. To secure its investment aid and future trade,China has taken policy implication. Whereas China takes this relation as mutually beneficial win-win situation, other competing bigpowers take it as security threat. To implement its business first policy, China ahead militarily too. As a developing leader of thethird world states, China wants to bring African states together to share its booming economy. Economy centered political relationswith African states will start the door of common allegation against Chinese human rights violation and reforming in governance.This paper, without neglecting the historical background of Sino-Afro relations, will highlight the Chinese political ambition behindthe scene of its economic relations with Africa and it also focus on mutual political interest in this relations. The motives of greatpowers in upcoming new great non-zero-sum game in Africa will also be forecasted in this paper.